IDENTIFICATION OF INTEREST USING THE SHOPEEPAY DIGITAL WALLET: PERCEPTION OF EASE OF USE AND RISK PERCEPTION - Sulasih, Sulasih; Parno, Parno; Suliyanto, Suliyanto (Journal of Management and Islamic Finance, 2024)
The digital wallet is a popular electronic payment system in Indonesia, with two main types: server-based and chip-based. The decision to adopt a digital wallet is influenced by several factors. This study employs the Technology Acceptance Model (TAM), which posits that the acceptance of information technology is primarily driven by two factors: perceived usefulness and perceived ease of use. In this study, the independent variables are perceived ease of use and perceived risk, while the dependent variable is interest in using the ShopeePay digital wallet. A quantitative approach was used, with primary data collected through a questionnaire completed by 100 respondents. The data was analyzed using a multiple linear regression model with SPSS software. The results indicate that both perceived ease of use and perceived risk significantly impact interest in using the ShopeePay digital wallet. This study contributes to the understanding of factors influencing the adoption of digital wallets in Indonesia, particularly focusing on ShopeePay.